3D printing of microbots, characterisation, and utilisation in combination with allicin against C. albicans biofilms - Harinash Rao; Pei Pei Chong; Priya Madhavan (Elsevier, 2023)
A major driving factor for antimicrobial resistance which leads to treatment failure for microbial infections ascribed to C. albicans are the formation of biofilms. 3D printing is a rapidly evolving innovation which could revolutionize drug delivery based on its unprecedented opportunity for targeted and improved delivery. Herein, we designed and 3D printed microbots via two photon-polymerisation. Subsequently, characterisation was performed and the activity of microbots independently and in combination with allicin against C. albicans biofilms were investigated. The microbots independently did not affect C. albicans biofilm formation and adhesion nor was there any significant synergistic interaction between microbots and allicin combination. However, this study has pioneered the utilisation of microbots for microbiological applications such as in combination with an antimicrobial to target biofilms. These prototype microbots will act as a guide for the next generation of microbots which will be functionalised to disrupt biofilms magnetically, enhancing allicin delivery and activity.